2020
DOI: 10.3390/geosciences10080307
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of 3D Metric Survey and GPR for the Diagnosis of the Trapezophoros with Two Griffins Attacking a Doe of Ascoli Satriano (Foggia, Italy)

Abstract: Protection and conservation are not feasible without a deeper knowledge of the cultural heritage of the subject of intervention. A careful analysis of documentation, a detailed visual inspection of surfaces, and a systematic diagnosis of the inner properties are the basis for planning preventive strategies of restoration. Digital noninvasive techniques represent an advantageous tool with useful outputs to estimate the state of health of cultural heritage in order to minimize the progress of degradation. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…results proved that around 40% of the volume of the sculpture base presented a state of conservation that was particularly worrying, since the overall measured average velocity was lower than 1500 m/s due to damage and fractures (Figure 18). Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe. The combined use of a 3D geometric survey and GPR analysis allowed assessment of Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe.…”
Section: Statue Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…results proved that around 40% of the volume of the sculpture base presented a state of conservation that was particularly worrying, since the overall measured average velocity was lower than 1500 m/s due to damage and fractures (Figure 18). Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe. The combined use of a 3D geometric survey and GPR analysis allowed assessment of Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe.…”
Section: Statue Case Studiesmentioning
confidence: 99%
“…Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe. The combined use of a 3D geometric survey and GPR analysis allowed assessment of Cozzolino et al [118] showed the results of a joint survey (photogrammetry and GPR) for the study and documentation of a stone trapezophoros with two griffins attacking a doe. The combined use of a 3D geometric survey and GPR analysis allowed assessment of the conservation condition of the trapezophoros.…”
Section: Statue Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations